The Relationship Of The Implementation Of Spirituality Aspects Of Nurses With The Fulfillment Of Spiritual Needs Inpatients At Imelda Hospital Medan - Damanik, Candra Meriani; Ritonga, Yuni Shanti; Gultom, Satriani H.; Naibaho , Eka Nugraha V. (SEAN Institute, 2024)
Nurses believe that humans are complete bio-psycho-socio-cultural and spiritual beings who respond to changes that occur, among other things, due to health problems and irregularities in meeting needs. The nurse seeks to help meet the client's spiritual needs as part of the client's overall needs, including by facilitating the fulfillment of the client's spiritual needs, even though the nurse and client do not have the same spiritual or religious beliefs. This study aims to determine the relationship between implementing aspects of nurses' spirituality and fulfilling the spiritual needs of inpatients at Imelda Hospital in Medan. The type of research used is descriptive correlation with a cross sectional study design. The research was conducted in April 2019. The population in this study was all 350 patients treated in the inpatient ward at the Imelda Workers Indonesia Hospital. The sampling technique in this research is a quota sampling technique, so the number of samples in this research is 35 people. The results of the analysis of the relationship between the application of spiritual aspects of nurses and the fulfillment of patients' spiritual needs showed that there were 25 (71.4%) respondents whose spiritual needs were fulfilled by the application of spiritual aspects of nurses well. Statistical tests using chi square obtained a p value <0.05, meaning there is a relationship between aspects of spiritual application and the fulfillment of spiritual needs. It is hoped that the results of this research can be used as a reference for Imelda Hospital in improving health services, especially the implementation/nursing care in meeting the spiritual needs of patients